The Role of Research in the Consolidation of Innovations - de Zubiría Samper, Julián (Instituto para la Investigación Educativa y el Desarrollo Pedagógico, IDEP, 2017)
The article analyzes the role of research in the consolidation of pedagogical innovations. Based on his thirty years of experience at the Alberto Merani Institute and his permanent contact with innovators in Latin America, the author finds five possible ways in which research can help to consolidate and expand the horizons of innovations: 1) Assessing the impacts achieved; 2) Grounding the ideas of the innovator; 3) Countering trends to traditionalism; 4) Becoming an excellent mechanism to control the fragility of innovation; 5) Broadening the horizons of innovation. This article is especially based on the experience and challenges faced by a pedagogical innovation case such as the Alberto Merani Institute.